Medical advances in hepatitis D therapy: molecular targets - Vogt, Amelie; Wohlfart, Sabrina; Urban, Stephan; Mier, Walter (International journal of molecular sciences, 2022)
An approximate number of 250 million people worldwide are chronically infected with hepatitis B virus, making them susceptible to a coinfection with hepatitis D virus. The superinfection causes the most severe form of a viral hepatitis and thus drastically worsens the course of the disease. Until recently, the only available therapy consisted of interferon-α, only eligible for a minority of patients. In July 2020, the EMA granted Hepcludex conditional marketing authorization throughout the European Union. This first-in-class entry inhibitor offers the promise to prevent the spread in order to gain control and eventually participate in curing hepatitis B and D. Hepcludex is an example of how understanding the viral lifecycle can give rise to new therapy options...